Accounting for Management: Planning and Control (Book). - Meyer, Philip E.; Moore, Robert W. (The Accounting Review, 1984)
Reviews the book "Accounting for Management: Planning and Control," 3rd ed., by Richard M. Lynch and Robert W. Williamson.